Electron Band Alignment at Interfaces of Semiconductors with Insulating Oxides: An Internal Photoemission Study. (13th February 2014) - Afanas'ev, Valeri V.
Abstract : Evolution of the electron energy band alignment at interfaces between different semiconductors and wide-gap oxide insulators is examined using the internal photoemission spectroscopy, which is based on observations of optically-induced electron (or hole) transitions across the semiconductor/insulator barrier. Interfaces of various semiconductors ranging from the conventional silicon to the high-mobility Ge-based (Ge, Si 1-x Ge x, Ge 1-x Sn x ) and A I I I B V group (GaAs, In x Ga 1-x As, InAs, GaP, InP, GaSb, InSb) materials were studied revealing several general trends in the evolution of band offsets. It is found that in the oxides of metals with cation radii larger than ≈ 0.7 Å, the oxide valence band top remains nearly at the same energy (±0.2 eV) irrespective of the cation sort. Using this result, it becomes possible to predict the interface band alignment between oxides and semiconductors as well as between dissimilar insulating oxides on the basis of the oxide bandgap width which are also affected by crystallization. By contrast, oxides of light elements, for example, Be, Mg, Al, Si, and Sc exhibit significant shifts of the valence band top. General trends in band lineup variations caused by a change in the composition of semiconductor photoemission material are also revealed.